Effect of grain shape on the jamming of two-dimensional silos - Goldberg, Ezequiel (2017)
We present discrete element method simulations of the discharge of silos in two dimensions. We study the effect of the grain shape on the clogging of small apertures, considering regular polygons and disks of equal mass. In particular, we analyze the avalanche size distribution and the jamming probability for disks, triangles, squares, pentagons, hexagons and heptagons as a function of the aperture size. We show that the jamming probability presents a non-linear response as a function of the number of vertexes of the polygons.